Faculty and its Impact on Critical Thinking Abilities of Undergraduate Medical Students – A Delphi Study - Ahmad Muqeem, Sadaf Sajid, Syma Arshad, Sofia Waheed Khan, Abdullah Ahmad, Hoorish Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To identify individual skills/attitude of faculty which influence fostering of critical thinking in undergraduate medical students Study Design: Modified Delphi Study Place and Duration of study: This study was carried out at University of Lahore from October 2018 to April 2019. Methodology: Delphi Study was used to develop consensus. Experts were MME/MHPE/ MCPS HPE qualified faculty members with 03 years of teaching experience. A draft questionnaire was developed on Google Forms after thorough literature review and sent to 05 experts for Pilot Study, construct validation and cognitive pretesting. A Wait Time of 04 weeks, rating of questions on 5 point Likert Scale and consensus criteria of 80% were defined before the start of study. SPSS 25 was used for data analysis. During 1st Round, draft questionnaire was amended in the light of opinion of experts to open ended questions and was sent to all the participants for their response. During 2nd Round, a new questionnaire was developed after data analysis and duly amended questionnaire was sent to the participants of Round 1. Results: A total of 27 experts were enrolled in the study. 17 experts (62.96%) responded during the first round. Consensus was achieved for 13 items (65%) out of 20. In the 2nd round, 15(88.23%) out of 17 responded. Consensus was achieved for all 7 items (100%). The study revealed that majority of our faculty lacks proper training and does not possess knowledge about various educational theories / principles and their application. They do not know how to act as facilitator, conduct tutorials, ask high order questions, reflect and provide constructive feedback. They do not give enough wait time to students after asking an open ended / higher order question. They are over committed with administrative work besides teaching. Conclusion: Individual skills / attitude of faculty hamper fostering of CT in undergraduate medical students. They are mainly due to lack of formal faculty training which should be addressed not only in the medical institutions but in the pre-medical schools as well to inculcate higher order critical thinking skills in students. Keywords: Critical Thinking (CT), Undergraduate Medical Students, Faculty, Reflections, Feedback